(untitled) - Dr. Kamaljeet Kaur (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Coronavirus is a pandemic, which is surviving worldwide. The only way to overcome this deadly disease is the lockdown. The lockdown is a state of isolation. Man is a social animal and do not like to live in Isolation. Humans are feeling like prisoners and facing depression symptoms due to Lockdown. Many people have lost their jobs and income sources. But every coin has two sides; similarly few positive things happened during Lockdown. People are spending maximum time with their family, doing work from home and the most important is the fall in Pollution. Coronavirus has worked as if a reset button for nature. The lockdown will give birth to new and improved humans and environment. Our research paper will focus that how Lockdown is positive for Environment. We will focus on metropolitan cities such as Delhi, Mumbai, Kolkata, Chennai and Chandigarh.